Bad Axe County : a novel - Galligan, John (Atria Books, 2019)
Fifteen years ago, Heidi White<U+2019>s parents were shot to death on their Bad Axe County farm. The police declared it a murder-suicide and closed the case. But that night, Heidi found the one clue she knew could lead to the truth<U+2014>if only the investigators would listen. Now Heidi White is Heidi Kick, wife of local baseball legend Harley Kick and mother of three small children. She<U+2019>s also the interim sheriff in Bad Axe. Half the county wants Heidi elected but the other half will do anything to keep her out of law enforcement. And as a deadly ice storm makes it way to Bad Axe, tensions rise and long-buried secrets climb to the surface. As freezing rain washes out roads and rivers flood their banks, Heidi finds herself on the trail of a missing teenaged girl. Clues lead her down twisted paths to backwoods stag parties, derelict dairy farms, and the local salvage yard<U+2014>where the body of a different teenage girl has been carefully hidden for a decade. As the storm rages on, Heidi realizes that someone is planting clues for her to find, leading her to some unpleasant truths that point to the local baseball team and a legendary game her husband pitched years ago. With a murder to solve, a missing girl to save, and a monster to bring to justice, Heidi is on the cusp of shaking her community to its core<U+2014>and finding out what really happened the night her parents died.